Association between medical marijuana legalization and sources of obtaining marijuana among adults in the United States. (2nd January 2022) - Lee, Yen-Han; Lee, Yi-Ting Hana; Chang, Yen-Chang; Liu, Ching-Ti; Arndt, Stephan
ABSTRACT: Background: Medical marijuana legalization (MML) has become more prevalent in the United States. This study examined the association between medical marijuana legalization and sources of obtaining marijuana among adults in the United States. Methods: Adult participants (age ≥ 18) from the 2018 wave of the National Survey on Drug Use and Health (NSDUH) were analyzed (n = 42, 669, weighted N = 247, 247, 786). We used two multinomial regression models to estimate the association. The first model controlled for sociodemographic variables, and the second model additionally included an interaction effect of participants' race with MML. Results: In the first model, participants residing in states with MML were positively associated with reporting lifetime marijuana use (but did not use in the past 12 months), buying marijuana, receiving marijuana for free or sharing with others, and growing marijuana on their own (all p < .01). With the interaction of participants' race, nonwhites residing in states with MML were negatively associated with reporting lifetime marijuana use and receiving marijuana for free or sharing marijuana with others (all p < .05). Conclusion: Policy makers should be aware of the sources of obtaining marijuana in the states with legalization of medical marijuana.